Kuantifikasi Kontribusi Faktor Iklim Terhadap Variasi Produktivitas Tanaman Kelapa Sawit - Pradiko, Iput; Hariyadi, Hariyadi; June, Tania (Pusat Penelitian Kelapa Sawit, 2023)
The yield of oil palm is heavily influenced by various climatic conditions, including rainfall (RF), radiation (Qs), temperature, and humidity. To quantify the impact of these factors, a study was conducted on a 15-year-old palm located in an oil palm estate in Pangkalan Lima Puluh Kota, West Sumatra, Indonesia. The study used climate data from 2011-2019 and yield data from 2015 and 2019. To determine the contribution of RF, Qs, and VPD / vapour pressure deficit, which was estimated from temperature and humidity, a computer-intensive importance metric developed by Lindemann, Merenda, and Gold (LMG metric) was utilized. The results showed that RF, Qs, and VPD collectively accounted for 50.16% of yield fluctuations at the study site. Furthermore, the contribution of climate factors on yield followed the order of VPD > Qs > RF.